Retinoids in cancer chemoprevention and therapy: Meta-analysis of randomized controlled trials - Chen, Shuting; Hu, Qinchao; Tao, Xiaoan; Xia, Juan; Wu, Tong; Cheng, Bin; Wang, Juan (Frontiers in Genetics, 2022)
Retinoids, natural and synthetic derivatives of vitamin A, have many regulatory functions in human body, including regulating cellular proliferation, differentiation, apoptosis. Moreover, retinoids have been used successfully for the treatment of certain malignancies, especially acute promyelocytic leukemia (APL) in adults and neuroblastoma in children. However, retinoids have not yet been translated into effective systemic treatments for most solid cancers. Some recent studies have shown that retinoids promote tumorigenesis. Therefore, we performed this meta-analysis to systematically evaluate the efficacy of retinoids in the chemoprevention and treatment of cancers. We performed literature search of several electronic databases, including PubMed, Embase and Cochrane Library from 2000 January to 2021 November. Various outcomes were applied to investigate the potential of retinoids for prevention and treatment of cancers. The primary outcomes in this study were disease recurrence and clinical response. The secondary outcomes included overall survival (OS), cancer development, disease progression and event-free survival. We identified 39 randomized controlled trials with 15,627 patients in this study. Our results showed that lower recurrence rate and better clinical response were obtained in retinoids treated patients with cancer or premalignancy as compared with control. The differences were statistically significant (RR=0.85, 95% CI=0.74-0.96, P=0.01; RR=1.24, 95% CI=1.03-1.49, P=0.02, respectively). Retinoids treatment was not associated with improvement in overall survival, cancer development, disease progression or event-free survival. Subgroup analysis conducted based on cancer type showed that patients benefited from retinoids treatment in APL, renal cell carcinoma, hepatocellular carcinoma, lung cancer, Kaposi sarcoma, and complete hydatidiform mole. No significant therapeutic effect was noted in head and neck cancer, acute myeloid leukemia (AML), melanoma, breast cancer, bladder cancer, cervical intraepithelial neoplasia (CIN) or cervical carcinoma. Subgroup analysis based on tumor classification demonstrated that retinoids group obtained a lower recurrence rate and better clinical response than control group in solid cancers. In conclusion, clinical application of retinoids was associated with reduction in disease recurrence and improvement in clinical response, illustrating that retinoids play a key role in cancer prevention and therapy. Further research is needed to broaden the utility of retinoids in other types of cancers.